Measurement of the 𝐷* longitudinal polarization in 𝐵0→𝐷*−⁢𝜏+⁢𝜈𝜏 decays - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Cocha Toapaxi, Carlos; De Cian, Michel; Glaser, Fabian; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Langenbruch, Christoph; Leverington, Blake; Marks, Jörg; et al. (Physical review, 2024)
The longitudinal polarization fraction of the 𝐷* meson is measured in 𝐵0 →𝐷*−⁢𝜏+⁢𝜈𝜏 decays, where the 𝜏 lepton decays to three charged pions and a neutrino, using proton-proton collision data collected by the LHCb experiment at center-of-mass energies of 7, 8 and 13 TeV and corresponding to an integrated luminosity of 5 fb−1. The 𝐷* polarization fraction 𝐹𝐷*𝐿 is measured in two 𝑞2 regions, below and above 7 GeV2/𝑐4, where 𝑞2 is defined as the squared invariant mass of the 𝜏⁢𝜈𝜏 system. The 𝐹𝐷*𝐿 values are measured to be 0.52 ±0.07 ±0.04 and 0.34 ±0.08 ±0.02 for the lower and higher 𝑞2 regions, respectively. The first uncertainties are statistical and the second systematic. The average value over the whole 𝑞2 range is 𝐹𝐷*𝐿=0.41±0.06±0.03. These results are compatible with the Standard Model predictions.
ATLAS Collaboration: R. Aaij, S. Bachmann, L. Carus, R. Caspary, C. Cocha Toapax, M. De Cian, F.C. Glaser, X. Han, S. Hansmann-Menzemer, C. Langenbruch, B. Leverington, J. Marks, M.P. Morgenthaler, M. Ruiz Diaz, G. Tuci, L. Uecker, D.J. Unverzagt, U. Uwer, L. Witola, Y. Zhao, A. Zhelezov [und zahlreiche weitere]
Gesehen am 19.12.2025